Partitioning of Bromelain from Pineapple Stem (Smooth Cayenne) by Aqueous Two Phase System and Its Application for Recovery and Purification of Polyhydroxyalkanoate - Kanokphorn Sangkharak (Science Faculty of Chiang Mai University, 2019)
Bromelain from pineapple stem was extracted using aqueous two phase system (ATPs). In addition, the application of bromelain for recovery and purification of polyhydroxyalkanoate (PHA) was also investigated. The optimal condition for bromelain partitioning was 15% polyethylene glycol (PEG)4000-20%K2HPO4. The highest activity recovery (80.14%) and enzyme purity was increased to 1.84-folds under optimal condition. The molecular weight of bromelain was 29 kDa. Bromelain yielded the highest activity when incubated with buffer pH 6.0 under 45°C. After purification and precipitation, the bromelain optimal pH changed from 6.0 to 7.0 and its optimum temperature was 50°C, however it kept activity even after 60°C. The activity of bromelain showed higher stability at pH 7.0-8.0 and was slightly stable at all pH levels tested. Its activity also decreased continuously with an increase of NaCl concentration. Partially purified bromelain was applied to recovery and purification of PHA from PHA-accumulating bacteria. The experiment was determined in 5 bacteria including both Gram-positive and Gram-negative strains. The result showed that bromelain was suitable for PHA purification. High PHA purity (82.7-96.5%) was observed in Gram-negative bacteria. The results were also compared with commercial bromelain. The lower efficiency was obtained from partially purified enzyme, but the content was not significantly different.